ISOLASI EUGENOL DARI BUNGA CENGKEH DAN SINTESIS EUGENIL ASETAT (2-METHOXY-4-(2-PROPEN-1-YL)-PHENYL ACETATE) - Yance Manoppo; H J Sohilait; Healthy Kainama (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
Isolation of eugenol from clove oil and synthesis of eugenyl acetate from eugenol had been concluded. Extraction of clove oil from clove flower by using petrolium benzene with sohxlet extraction method so obtained 33.82%. The isolation of eugenol with NaOH yields 32.07% with purity 97.47% by gas chromatography. Esterification of eugenol with acetate anhydride and sodium acetate anhydride as catalyst yields eugenyl acetate 51,67% with purity 98.38%. Elucidation of these structures were analyzed by FTIR, 1H-NMR and MS spectrofotometry